Hakikat Alam Semesta Menurut Filsuf Islam - Siti Maunah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2019)
The purpose of this research is to find out the views of Islamic philosophers on the nature of the universe. The method used is a qualitative method with a literature study. Data collection is done by collecting literacy from various sources such as books, journals and other literacy. The results of this study are according to Al-Ghozali, the existence of nature begins from the non-existent so that nature is not qadim and created by Allah SWT. Al-Farabi and Ibn Sina stated that Nature was qadim because Allah created it from the beginning. According to Ibn Rushd, nature consists entirely of objects and forms which are essentially eternal (eternal eternal), but the divinity is far from the divine essence. Whereas according to Ibn Tufail, nature is entirely a result and created by God without time.